RESPON PERTUMBUHAN DAN HASIL JAMUR TIRAM PUTIH (Pleurotus ostreatus) TERHADAP SUBTITUSI SEKAM PADI DAN PEMBERIAN SUPLEMEN ORGANIK - Malik Tsaqafi; Darso Sugiono; Ani Lestari (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
White oyster mushroom (Pleurotus ostreatus) is a type of local mushroom that has been and is being developed in Indonesia. Efforts to find alternative media for sawdust if it is difficult to obtain or not available and the addition of nutrients from the outside by giving organic supplements to increase the growth and development of oyster mushrooms. The experiment was carried out in Bahagia Village, Babelan District, Bekasi Regency. The research method used was an experimental method with a single factor Randomized Block Design (RBD). There were 10 treatment, namely A (without the addition of media + aquades 100%), B (15% rice husk + 25% organic supplement), C (15% rice husk + 50% organic supplement), D (15% rice husk + 75% organic supplement), E (30% rice husk + 25% organic supplement), F (30% rice husk + 50% organic supplement), G (30% rice husk + 75% organic supplement), H (45% rice husk + 25% organic supplement), I (45% rice husk + 50% organic supplement) and J (45% rice husk + 75% organic supplement). The results showed that there was a significant effect of rice husk substitution and organic supplementation on the number of fruit clumps per baglog, fruit cap diameter per baglog, and fresh weight of mushrooms per baglog. Treatment C (15% rice husk + 50% organic supplement) gave the highest results on the parameters of the number of fruit clumps per baglog (1.00), fruit cap diameter per baglog (6.03 cm),  fresh weight of mushrooms per baglog (60.54 grams).